(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Translation has been widely used as a method in language teaching for centuries. It involves the conversion of words or texts from one language to another, aiding learners in understanding and producing accurate language expressions. This article explores the various translation methods in teaching and discusses their benefits and limitations in language acquisition.